Urea treatment of rice straw at elevated temperature and pressure: Effects on fiber content, rumen fermentation and digestibility - Jayanegara, A.; Ayinda, R. S. K.; Laconi, E. B. (Diponegoro University, 2017)
The objective of this study was to apply urea treatment of rice straw at elevated temperature and pressure (121oC; 1.4 atm) and at short treatment period (30 or 60 min) in comparison to conventional urea treatment (4 weeks incubation). Rice straw was subjected to the following treatments: RS1: untreated rice straw (control), RS2: RS1+1% urea (no incubation), RS3:RS1+1% urea (4 weeks incubation), RS4: RS2+autoclave 30 min, RS5: RS3+autoclave 30 min, RS6: RS2+autoclave 60 min, RS7: RS3+autoclave 60 min. The samples were analyzed for fiber contents and incubated in vitro. Data were analyzed using analysis of variance and Duncan’s post-hoc test. Results showed that urea treatments (RS3-RS7) did not change NDF and ADF contents of rice straw in comparison to control. Urea treatment in autoclave for 30 min (RS4) increased rice straw IVDMD and IVOMD by 23.3% and 25.6% as compared to control, respectively (P<0.05). Extension of the incubation period to 60 min (RS6) did not improve further the IVDMD and IVOMD. Treatments did not change pH values and NH3 concentrations. Urea treatment (RS3-RS7) increased total VFA concentration in comparison to control (P<0.05). It was concluded that urea treatment using autoclave for 30 min may replace conventional urea treatment to improve nutritional value of rice straw.